A enunciação no discurso religioso em testemunhos de fiéis da IURD - Lacerda, Noara Pedrosa (2010)
The enunciation in the religious discourse in the faithful´s testimonies from the Igreja Universal do Reino de Deus is an analysis that points out to a new research perspective concerning religious studies. The present work, therefore, is a different insight about the religious phenomenon. It focuses on the prosperity theme present in the faithful´s testimonies from the mentioned church. Such corpus was displayed on this church s site in 2009. Our main aim, thus, was to analyze the meaning of the religious discourse in these people s enunciation process. The religious texts do constitute a wide research field from the Sociology related to the religion area, with its interpretation, favoring the mutual interaction between religion and society; the perspective of Theology in regard to hermeneutics and their interpretations of biblical principles, according to Friedrich Scheleiermacher (1768-843) and Boff (2005); to the linguistic and discursive perspective, being still very little exploited. Concerning the sociological point of view theoretical basis, we can mention Queiroz (1976); Bourdieu (2007); Wilges (1987/1988) and Bittencourt Filho (2003), among others in the area. As to the linguistic and discursive field, we can find some theoretical support in Bakhtin´s enunciation theory and dialogism (1972/2003); Brait (1996), as well as in an analysis of the religious discourse and the ways in which it is processed (ORLANDI, 1987). The Igreja Universal do Reino de Deus owns a persuasive discourse and it revisits the Words of Scripture so as to have support to its instant prosperity and happiness proposal. Such fact has somewhat directed our interest concerning this research, once we tried to study and understand the way the religious discourse, present in these texts, can characterize the persuasion modes and, therefore, reframe hope and prosperity in the selected testimonies. Thus, in an effort to fulfill our aims, some bibliographical surveys, concerning the enunciation theory through the Bakhtinian theoretical perspective, were made. Besides, we also carried out some research on the religious discourse theory. Apart from this, we selected our corpus, which was based on the faithful´s testimonies from the Igreja Universal do Reino de Deus, displayed on this church s official site. Though our analysis we could realize that both the persuasion as well as the act of convincing people are present in the religious discourse of the mentioned church. We can verify the presence of different discursive voices, which are somewhat articulated, marking the religious discourse enunciation. Besides, we could verify that it enables the perception of discourse not only as a theological or religious analysis object but it can be thought as related to other areas, receiving significant contributions to the renewal of the religious study. We present, therefore, a work that was articulated as an effort to enrich some approaches in the religious field outside the specific fields of theology and sociology, even though it does not abandon or disregard their contributions.